Path analysis under multicollinearity in green pepper - de Carvalho, Claudio Guilherme Portela; Oliveira, Valter Rodrigues; Cruz, Cosme Damião; Casali, Vicente Wagner Dias (Pesquisa Agropecuaria Brasileira, 1999)
The main goals of this work were: a) to display genotype correlations in direct and indirect effects of primary and secondary components on the production of fruits, in green pepper (Capsicum annuum L.) genotypes, by mean of path analysis; b) to compare alternative methods of estimation of the path coefficients to avoid the adverse effects of multicollinearity. Based on the magnitude of direct and indirect effects, none of the primary or secondary components showed to be more important in the selection of more productive genotypes. In segregating populations, the character height of the plant might be useful in correlated response, by means of indirect selection. In the occurrence of moderate to severe multicollinearity between the characters, the elimination of variables from the regression model and the ridge path analysis showed to be efficient in reducing the high variances of the path coefficients found. However, when several variables need to be eliminated, the disposal process becomes difficult and many analysis might be necessary. Ridge path analysis, although, should by-pass the adverse effects of multicollinearity, without having great reduction on the coefficient determination values of the regression models.